Progress in Pathogenesis of Proteinuria. (24th May 2012) - Zhang, Aihua; Huang, Songming
Abstract : Aims . Proteinuria not only is a sign of kidney damage, but also is involved in the progression of renal diseases as an independent pathologic factor. Clinically, glomerular proteinuria is most commonly observed, which relates to structural and functional anomalies in the glomerular filtration barrier. The aim of this paper was to describe the pathogenesis of glomerular proteinuria. Data Sources . Articles on glomerular proteinuria retrieved from Pubmed and MEDLINE in the recent 5 years were reviewed. Results . The new understanding of the roles of glomerular endothelial cells and the glomerular basement membrane (GBM) in the pathogenesis of glomerular proteinuria was gained. The close relationships of slit diaphragm (SD) molecules such as nephrin, podocin, CD2-associated protein (CD2AP), a-actinin-4, transient receptor potential cation channel 6 (TRPC6), Densin and membrane-associated guanylate kinase inverted 1 (MAGI-1), α 3 β 1 integrin, WT1, phospholipase C epsilon-1 (PLCE1), Lmx1b, and MYH9, and mitochondrial disorders and circulating factors in the pathogenesis of glomerular proteinuria were also gradually discovered. Conclusion . Renal proteinuria is a manifestation of glomerular filtration barrier dysfunction. Not only glomerular endothelial cells and GBM, but also the glomerular podocytes and their SDs play an important role in the pathogenesis of glomerular proteinuria.